MÖSSBAUER CHARACTERIZATION OF IRON ORE IN NATURAL ROCKS - Trujillo Sáenz, Carolina (2000)
This work deals with the characterization study by 57Fe Mössbauer spectroscopy of natural rocks with high content of iron oxides and iron compounds such as magnetite Fe3O4 and magnetite with chalcopirite Fe3O4.CuFeS2. This study presents also a comparative study using X-ray diffraction. The diffraction pattern belonging to magnetite was analyzed with the Rietveld refinement method obtaining results that agree with the information available for natural samples. Mössbauer measurements at low temperatures were undertaken with the purpose of identifying the different strucural sites for Fe ions in samples with high magnetite content.